2020
DOI: 10.1007/s12525-020-00432-5
|View full text |Cite
|
Sign up to set email alerts
|

Frontline robots in tourism and hospitality: service enhancement or cost reduction?

Abstract: Robots are being implemented in many frontline services, from waiter robots in restaurants to robotic concierges in hotels. A growing number of firms in hospitality and tourism industries introduce service robots to reduce their operational costs and to provide customers with enhanced services (e.g. greater convenience). In turn, customers may consider that such a disruptive innovation is altering the established conditions of the service-provider relationship. Based on attribution theory, this research explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
135
0
12

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 160 publications
(150 citation statements)
references
References 93 publications
(153 reference statements)
3
135
0
12
Order By: Relevance
“…The third finding of the study showed that hotel customers' perceived value of using robots made them more willing to use robots. For example, the fact that robot waiters equipped with artificial intelligence recognize customers and greet them by name created a positive perception of the service provided to customers [77]. A service robot that addressed customers with a smile and polite language was perceived by customers as more friendly and approachable [34].…”
Section: Discussionmentioning
confidence: 99%
“…The third finding of the study showed that hotel customers' perceived value of using robots made them more willing to use robots. For example, the fact that robot waiters equipped with artificial intelligence recognize customers and greet them by name created a positive perception of the service provided to customers [77]. A service robot that addressed customers with a smile and polite language was perceived by customers as more friendly and approachable [34].…”
Section: Discussionmentioning
confidence: 99%
“…Service robots can be structured to provide unique and novel experiences that enable competitive advantage and brand positioning [15,18,28]. Belanche, Casaló, and Flavián [31] state that the incorporation of service robots results in service enhancement and can also reduce transaction times, provide faster assistance, and increase customers' intentions to use and recommend service robot usage. A range of such studies highlights that smart environments enhance customer experiences and quality of service delivery [32,33].…”
Section: Enhanced Service Experiencesmentioning
confidence: 99%
“…The needs and interests of visitors also need to be considered in decision making. For instance, service robots are useful to deploy to customers who like to see consistent service quality and efficient service provision (e.g., speedy delivery of food to hotel rooms and tables) [31]. These types of human-robot interactions (HRIs) can help to enhance positive perceptions of robotization of tourism experiences.…”
Section: Transformative Changes In the Hospitality And Tourism Domainmentioning
confidence: 99%
See 2 more Smart Citations